2013
DOI: 10.1042/bst20120351
|View full text |Cite
|
Sign up to set email alerts
|

AMPK: opposing the metabolic changes in both tumour cells and inflammatory cells?

Abstract: AMPK (AMP-activated protein kinase) is a sensor of cellular energy status that appears to have arisen during early eukaryotic evolution. In the unicellular eukaryote Saccharomyces cerevisiae, the AMPK orthologue is activated by glucose starvation and is required for the switch from glycolysis (fermentation) to oxidative metabolism when glucose runs low. In mammals, rapidly proliferating cells (including tumour cells) and immune cells involved in inflammation both tend to utilize rapid glucose uptake and glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…It is becoming increasingly apparent that cells can couple inflammatory status to the availability of nutrients (51) (52). Conversely, the mechanisms by which nutrient availability can regulate inflammation remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming increasingly apparent that cells can couple inflammatory status to the availability of nutrients (51) (52). Conversely, the mechanisms by which nutrient availability can regulate inflammation remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Stresses that deplete energy and increase the intracellular AMP-to-ATP ratio induce allosteric activation of AMPK (1,2), promoting conformational changes that make the enzyme a better substrate for upstream kinases, which phosphorylate its Thr-172 residue and further activate AMPK. In its activated state, AMPK shuts down processes that consume energy and upregulates energy-producing pathways in an attempt to restore intracellular ATP levels (1,2,3). One of the well-described effects of AMPK is the inhibition of acetylCoA-carboxylase (ACC), an enzyme responsible for the conversion of acetyl-CoA to malonyl-CoA in de novo fatty acid biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…AMP-activated protein kinase (AMPK) is a metabolic stress-sensing cytoplasmic enzyme composed of an a-catalytic and two regulatory subunits (b and g) (1). Stresses that deplete energy and increase the intracellular AMP-to-ATP ratio induce allosteric activation of AMPK (1,2), promoting conformational changes that make the enzyme a better substrate for upstream kinases, which phosphorylate its Thr-172 residue and further activate AMPK.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes of the cytokine profile in the microenvironment induce macrophage subsequently shift their functional phenotypes, and display highly balanced patterns of inflammatory features (7,8). The AMP-activated protein kinase (AMPK) has been well established as a regulator of energy homeostasis in eukaryotic cells and recent research suggests an important role of AMPK as a counterregulator in many inflammatory processes (9)(10)(11)(12)(13). Our previous studies have shown that AMPK responds to either pro-or anti-inflammatory stimuli and plays a key regulatory role in macrophage and dendritic cell (DC) inflammatory functions (14,15).…”
Section: Introductionmentioning
confidence: 99%